Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
y = 2x + 1 ;
y - 3 = - 3(x - 1) ; y = - 3x + 6 ;
Step-by-step explanation:
Given the data:
Sidewalk 1:
x __ y
2 _ 5
0 _ 1
Sidewalk 2:
x __ y
1 _ 3
3 _ -3
Equation for sidewalk 1 in slope - intercept form:
Slope intercept form:
y = mx + c
c = intercept ; m = slope
m = (change in y / change in x)
m = (1 - 5) / (0 - 2) = - 4 / - 2 = 2
Y intercept ; value of y when x = 0
(0, 1) ; y = 1
Hence, c = 1
y = 2x + 1
Sidewalk 2:
Point slope form:
y - y1 = m(x - x1)
m = slope
m = = (-3 - 3) / (3 - 1) = - 6/2 = - 3
Point (x1, y1) = (1, 3)
y - 3 = - 3(x - 1)
To slope intercept form:
y - 3 = - 3(x - 1)
y - 3 = - 3x + 3
y = - 3x + 3 + 3
y = - 3x + 6
Since the slope of both lines are different, intersection will be at single point and will have a single solution. This makes it independent.
Using substitution method :
y = 2x + 1 - - - (1)
y = - 3x + 6 - - - (2)
Substitute (1) into (2)
2x + 1 = - 3x + 6
2x + 3x = 6 - 1
5x = 5
x = 1
From (1)
y = 2(1) + 1
y = 2 + 1
y = 3
Coordinate of the point of intersection = (1, 3)
Answer: Use Mathaway it helps with these questions
Step-by-step explanation:
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.